2015
DOI: 10.1186/s12947-015-0035-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of calcium score and coronary flow velocity reserve in asymptomatic diabetic patients

Abstract: BackgroundThe risk stratification of patients with diabetes mellitus (DM) is a major objective for the clinicians, and it can be achieved by coronary flow velocity reserve (CFVR) or with coronary artery calcium score (CS). CS evaluates underlying coronary atherosclerotic plaque burden and CFVR estimates both presence of coronary artery stenosis and microvascular function. Consequently, CFVR may provide unique risk information beyond the extent of coronary atherosclerosis.AimOur aim is to assess joint prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Transthoracic CFVR is a versatile, reproducible, and noninvasive tool for evaluation of microcirculation in the absence of epicardial stenosis [9,17,[24][25][26][27]. Reduced CFVR is an important phenomenon in HCM, since inadequate increase of myocardial blood flow on demand predisposes HCM patients to recurrent myocardial ischemia [9,16,[28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic CFVR is a versatile, reproducible, and noninvasive tool for evaluation of microcirculation in the absence of epicardial stenosis [9,17,[24][25][26][27]. Reduced CFVR is an important phenomenon in HCM, since inadequate increase of myocardial blood flow on demand predisposes HCM patients to recurrent myocardial ischemia [9,16,[28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Higher NT-proBNP values were strongly predictive and associated with high CAC scores of CVD, where high NT-proBNP was associated with depressed systolic and diastolic function, while CAC correlated with atheromatous plaque formation. Dikic et al [ 58 ] found the association between coronary flow velocity reserve (CFRV) and CAC score in 200 asymptomatic and diabetic patients. In diabetic patients with a high CAC score, there was a significant correlation between CFRV and total CS compared to non-diabetics, where there was no such correlation.…”
Section: Resultsmentioning
confidence: 99%
“…The main findings and conclusions of the selected studies varied from each other; most of them agree that CAC was an excellent tool. In contrast, others believe that it was not always adequate [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ] or evaluated if it was associated with other imaging methods or biomarkers [ 20 , 58 , 60 ] could suggest an inaccurate prognosis. Most of the studies indicated a strong correlation between the increase in the CAC score and the occurrence of cardiac events; in particular, the patients most at risk were those with CAC 400–1000 or >1000.…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, we measured the CCS, which has been recognized as a good predictor of cardiovascular disease in asymptomatic patients. 19 …”
Section: Discussionmentioning
confidence: 99%